2018
DOI: 10.1039/c7ra13244a
|View full text |Cite
|
Sign up to set email alerts
|

Copper-doped lanthanum manganite La0.65Ce0.05Sr0.3Mn1−xCuxO3 influence on structural, magnetic and magnetocaloric effects

Abstract: Bulk nanocrystalline samples of La0.65Ce0.05Sr0.3Mn1−xCuxO3 (0 ≤ x ≤ 0.15) manganites are prepared by the sol–gel based Pechini method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 53 publications
4
7
1
1
Order By: Relevance
“…This can be correlated with the increasing concentration of Mn 4+ ion, which has the smallest ionic radius within the samples, due to the substitution of La 3+ by K + ion. Similar cases where the unit cell volume of LMO-based compounds decreased due to substitution by larger ion have been observed by Shaikh and Varshney in La 1−x K x MnO 3 (x = 0.1; 0.125; and 0.15) compounds and Chebanee et al in La 0.65 Ce 0.05 Sr 0.3 Mn 1−x Cu x O 3 (0 ≤ x ≤ 0.15) compounds [39,40]. Substitution by K + ion also increases the < r A > from 1.243 to 1.310 for LKBS-0 and LKBS-20, respectively.…”
Section: Structural and Morphology Analysissupporting
confidence: 78%
“…This can be correlated with the increasing concentration of Mn 4+ ion, which has the smallest ionic radius within the samples, due to the substitution of La 3+ by K + ion. Similar cases where the unit cell volume of LMO-based compounds decreased due to substitution by larger ion have been observed by Shaikh and Varshney in La 1−x K x MnO 3 (x = 0.1; 0.125; and 0.15) compounds and Chebanee et al in La 0.65 Ce 0.05 Sr 0.3 Mn 1−x Cu x O 3 (0 ≤ x ≤ 0.15) compounds [39,40]. Substitution by K + ion also increases the < r A > from 1.243 to 1.310 for LKBS-0 and LKBS-20, respectively.…”
Section: Structural and Morphology Analysissupporting
confidence: 78%
“…For a eld of 50 kOe, the Sr-0.18 compound exhibit a DS M value of 4.61 J kg À1 K À1 at 310 K, and for Sr-0.27 compound, the DS M reaches a maximum value of 4.11 J kg À1 K À1 at 276 K. In our previous work, we reported a DS M value of 4.78 J kg À1 K À1 at 364 K for the pristine compound and 5.08 J kg À1 K À1 at 352 K for Sr-0.09 compound for a eld change of 50 kOe. 37 However, in the present case, we have achieved a near room temperature (310 K) MCE with a signicant DS M value (4.61 J kg À1 K À1 ) for Sr-0.18 compound which is larger than that reported for numerous perovskite manganites 29,31,35,45,47 Apart from the spin, charge and orbital ordering, the conventional DE interaction is the only favourable mechanism behind the entropy change in the pristine compound. 37 However, from the magnetization and magnetocaloric properties, it can be understood that the presence of Mn 2+ ions in decient compounds enhances the ferromagnetism and DS M due to the multiple DE interaction via Mn 3+ -O 2À -Mn 2+ -O 2À -Mn 4+ path.…”
Section: Resultscontrasting
confidence: 62%
“…This indicates that the strength of the competing exchange interactions and magnetic properties are eventually affected by different factors such as rare Earth substitution at the A-site, replacement of manganese by other transition elements, the introduction of deciency at A and A 0sites, etc. [28][29][30][31][32][33][34][35][36][37] Recently, many reports have demonstrated that the creation of deciency at the rare Earth and alkaline rare Earth sites alter the Mn 2+ /Mn 3+ /Mn 4+ ratio which severely affect the magnetic and magnetocaloric properties. [37][38][39][40][41][42][43][44][45][46][47][48][49] The structure of manganites is imperfect and contain vacancy type point defects, called Schottky defects due to the cyclic temperature changes during synthesis and sintering process.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, we will refer to one of the most-used macroscopic techniques to characterize magnetic materials: direct measurement of magnetization as a function of temperature and applied field. This technique offers vast information regarding the type of transition [35][36][37], transition temperature [38,39], magnitude of the magnetic moments [22,38,40,41], and the possible presence of clusters in the PM region, which is quite characteristic of manganites. Next, we will present results on the use of this technique in manganites.…”
Section: Macroscopic Magnetism: Mt H ðþmentioning
confidence: 99%